Profil Technological Pedagogical Content Knowledge Guru Ekonomi: Analisis Deskriptif Tujuh Komponen Pengetahuan - Lestari, Dian; Achmadi; Syamsuri (Paedagogie, 2026)
This study aims to describe the profile of teachers' Technological Pedagogical Content Knowledge (TPACK) based on seven components, namely Technological Knowledge (TK), Pedagogical Knowledge (PK), Content Knowledge (CK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), Pedagogical Content Knowledge (PCK), and Technological Pedagogical Content Knowledge (TPACK), without examining the relationships or effects between variables. This study employed a quantitative descriptive approach using a survey method. Data were collected through a closed Likert-scale questionnaire distributed to 253 economics teachers affiliated with the Subject Teacher Working Group (MGMP) for Economics. Data were analyzed descriptively using mean scores, standard deviations, and a three-level categorization (low, moderate, high) based on mean and standard deviation norms. The results show that the majority of teachers fall into the moderate category across all seven TPACK components, with Technological Content Knowledge (TCK) showing the relatively highest achievement and Pedagogical Knowledge (PK) showing the relatively lowest achievement, particularly on the indicator of understanding students characteristics. The findings indicate that teachers ability to integrate technology with subject content has developed reasonably well, whereas pedagogical competence oriented toward individual student needs still requires strengthening through continuous professional development.